Civic capital in two cultures: The nature of cooperation in Romania and USA - Tore Ellingsen; Benedikt Herrmann; Martin A. Nowak; David G. Rand; Corina E. Tarnita (Center for Economic Studies and ifo Institute (CESifo), 2012)
We experimentally investigate the nature of cooperation in various repeated games, with subjects from Romania and USA. We find stark cross-country differences in the propensity to sustain multilateral cooperation through bilateral rewards and punishments. U.S. groups perform well because sufficiently many cooperators are willing to discipline free riders. Romanian cooperators are less prone to jeopardize their productive bilateral relationships for the benefit of the group, collectively failing to provide adequate discipline. Our analysis indicates that the performance differences constitute a group-level phenomenon, being largely due differences in shared beliefs rather than differences in individuals' preferences.
Keywords: D02; D03; 330; Kulturelle Identität; Social Capital; Kooperation; Wiederholte Spiele; Test; Vergleich; Rumänien; USA